Factual Model of Internal Quality Assurance System of Private Higher Education Institutions in Indonesia - Andi Mursidi; Tri Joko Raharjo; Sugiyo Sugiyo; Arief Yulianto (STKIP Singkawang, 2020)
Quality has increasingly become an important success determiner for higher education institutions. The education quality highly depends on the quality of all management systems run by the higher education institutions. This research aims at explaining the factual model and identifying the main factors influencing the implementation and development of quality assurance system of private higher education institutions in West Kalimantan Province, Indonesia. Research and Development (R&D) method was used as the research methodology to develop the model. Data collection processes start by interviewing the stakeholders of internal quality assurance system at higher education institutions and then distributing questionnaires related to the implementation of internal quality assurance system at each higher education institution. The collected data was then analyzed and synthesized into the factual model. The obtained factual model consisted of three steps: planning, implementing, and evaluating the internal quality assurance. From this factual model, it is revealed that the implementation of internal quality assurance system of private higher education institutions in West Kalimantan Province, Indonesia has not completely become a part of higher education institution accountability orienting on the higher education quality assurance, but more on the temporary purposes, such as higher education institution accreditation purposes.